First-in-man application of Liwen RF™ ablation system in the treatment of drug-resistant hypertrophic obstructive cardiomyopathy - Wang, Zihao; Zhao, Rong; Sievert, Horst; Ta, Shengjun; Li, Jing; Bertog, Stefan; Piayda, Kerstin; Zhou, Mengyao; Lei, Changhui; Li, Xiaojuan; Liu, Jiani; Xu, Bo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: This study sought to evaluate the clinical applicability of the Liwen RFTM ablation system for percutaneous intramyocardial septal radiofrequency ablation (PIMSRA). Background: Data on new cardiac radiofrequency ablation devices for the treatment of hypertrophic obstructive cardiomyopathy (HOCM) are limited. Methods: From July 2019 to July 2020, a total of 68 patients with drug-resistant HOCM, who underwent PIMSRA with the Liwen RFTM ablation system, which has an ablation electrode of stepless adjustable length, were prospectively enrolled. Safety endpoints included, amongst others, the occurrence of pericardial effusion and/or hemorrhage, cardiac arrhythmias, device failure and procedural death. The reduction in left ventricular outflow tract (LVOT) gradients at 12 months follow-up were used as a surrogate marker for device efficacy. Results: All procedures were technically successful. The total energy output time of the system was 75.8 (IQR: 30.0) minutes, and the average power was 43.61 ± 13.34 watts. No ablation system error occurred. The incidence of pericardial effusion or hemorrhage, transient arrhythmia and resuscitation was 8.8%, 39.7% and 1.5% during procedure, respectively. None of the patients died. During 30-day follow-up, there were no complications with the exception of a pericardial effusion in one patient (1.5%). No further complications were reported after 30 days. The patients' resting [baseline: 75 (IQR: 48) vs. 12-months:12 (IQR: 19) mmHg, p < 0.001] and provoked [baseline: 122 (IQR: 53) vs. 12-months: 41 (IQR: 59) mmHg, p < 0.001] LVOT gradients decreased significantly during follow-up. Conclusion: In this study, we demonstrate the safety and feasibility of the Liwen RFTM ablation system to treat HOCM. The system allows for significant and sustainable LVOT gradient reduction during 12-months of follow-up. Hence, the Liwen RF ablation system is a promising new device that has the potential to become an alternative to existing septal reduction concepts in HOCM patients.